Data and computer communications - Stallings, William (Prentice-Hall, 2000)
Provides a clear and comprehensive survey of the whole field of data communications and a tutorial on leading-edge network technologies and protocols. Offers complete and detailed assessment of critical technical areas in data communications, wide-area networking, local area networking, and protocol design. DLC: Data transmission systems.